2017
DOI: 10.1590/1982-2554201730301
|View full text |Cite
|
Sign up to set email alerts
|

Idade penal no jornalismo de referência: os sentidos centrais na cobertura do debate sobre redução da maioridade penal

Abstract: Este é um artigo publicado em acesso aberto (Open Access) Resumo: O artigo se vale de uma perspectiva discursiva para compreender os fenômenos que envolvem jornalismo e segurança pública. Para tal, analisamos os núcleos de sentido que mais apareceram no discurso jornalístico de referência no debate sobre redução da maioridade penal, estimulado, dentre outros fatores, pela votação da PEC 171/1993. A observação foi realizada no período de 01 de junho a 05 de julho de 2015 nos jornais Folha de S. Paulo, O Globo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 1 publication
0
8
0
2
Order By: Relevance
“…Another three studies (Campos, 2009;Dias, 2017;Espíndula et al, 2006) indicated that the print media (newspapers and magazines) also corroborate with preconceived images about adolescents in confl ict with the law. In one of them (Campos, 2009), a study was conducted on the news stories in the Veja magazine and in the Folha de São Paulo newspaper, analyzing reports about crimes of great repercussion carried out by adolescents.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Another three studies (Campos, 2009;Dias, 2017;Espíndula et al, 2006) indicated that the print media (newspapers and magazines) also corroborate with preconceived images about adolescents in confl ict with the law. In one of them (Campos, 2009), a study was conducted on the news stories in the Veja magazine and in the Folha de São Paulo newspaper, analyzing reports about crimes of great repercussion carried out by adolescents.…”
Section: Resultsmentioning
confidence: 94%
“…In relation to the results found, it was evidenced that, from diff erent theoretical and methodological perspectives, the majority of the articles (Campos, 2009;Corte Real & Conceição, 2013;Dias, 2017;Espíndula et al, 2006;Petry & Nascimento, 2016;Scisleski et al, 2015;Silva & Hüning, 2015) described how diff erent subjects (parliamentarians, legal operators, professionals of the socio-educational system, students, users of social networks, etc.) perceived the phenomenon of juvenile criminality, forming a kind of mosaic with stereotypes of adolescents in confl ict with the law.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations